Quantitative assessment of current trends in water use in Volyn region - Fesyuk, V. O.; Moroz, I. A. (Man and Environment. Issues of Neoecology, 2025)
Purpose. To carry out a quantitative assessment of the main trends in water use in Volyn Region, analyze the dynamics of water withdrawal across key sectors  and identify the major factors influencing changes in the structure and volumes of water resource use.Methods. Statistical analysis, systems approach, predictive modelling and scenario analysis.Results. The water balance of Volyn Region is non-deficit, and available resources fully meet regional needs. In 2024, total water withdrawal reached 45.71 million m³, of which 36.3 million m³ were groundwater. Only about 4% of their estimated reserves are currently used. The main water users are the municipal sector (50%), agriculture, and industry. A key issue is high water losses during transportation (nearly 17%). The volume of discharged wastewater amounted to 29.08 million m³, most of which was treated. Wastewater treatment facilities operate close to their capacity, creating risks of declining water quality in the Pripyat and Western Bug rivers. Negative impacts include local excesses of biogenic substances and challenges associated with decentralized water supply. In general, the region's water management system is stable, but it needs modernization of treatment facilities, water supply and wastewater networks, and strengthening of environmental control.Conclusions. Hydroecological problems in Volyn Region are complex and stem from worn-out infrastructure, increasing wastewater volumes, and agricultural impacts, resulting in reduced natural self-purification capacity of water bodies. At the same time, positive trends are observed: the development of water reuse, modernization of treatment facilities, and more efficient technologies. Priorities include reducing water losses, upgrading treatment systems, expanding closed water-use cycles in industry, promoting water-saving practices in agriculture, implementing digital monitoring, integrated water management, and strengthening public involvement in addressing water-use challenges.